Serum creatinine concentration and creatinine-based estimation of glomerular filtration rate in athletes - Banfi, G.; Del Fabbro, M.; Lippi, G. (Sports Medicine, 2009)
Since serum creatinine concentration test results in athletes can sometimes be abnormal, correct test interpretation needs to take account of the sportsman's status, as well as the transient exercise-induced changes in creatinine and the marked differences in creatinine levels among athletes competing in different sport disciplines. Serum creatinine concentration in athletes is related to body mass index, so the use of general population reference ranges should not be recommended in sports medicine. This does not necessarily imply, however, that specific creatinine reference ranges for athletes need to be defined.